Biological isolation and characterization of Catharanthus roseus (L.) G. Don methanolic leaves extracts and their assessment for antimicrobial, cytotoxic, and apoptotic activities - Somashekara Rajashekara; Dondapati Reena; Mullahalli Venkataramareddy Mainavi; Locheruvapalli Srinivasa Sandhya; Utpal Baro (BMC, 2022)
Highlights • The methanolic leaf extracts of the Catharanthus roseus plants contain secondary metabolites. • CrPLE extracts showed antimicrobial and anticancer activities. • The use of Catharanthus roseus plants as a "natural herbal resource" in the pharmaceutical and pharmacological industry has been validated and further expanded.